Extracorporeal membrane oxygenation support in oncological thoracic surgery - Mangiameli, Giuseppe; Testori, Alberto; Cioffi, Ugo; Alloisio, Marco; Cariboni, Umberto (Frontiers in Oncology, 2022)
The use of extracorporeal lung support (ECLS) during thoracic surgery is a recent concept that has been gaining increasing approval. Firstly introduced for lung transplantation, this technique is now increasingly adopted also in oncological thoracic surgical procedures. In this review, we focus on the cutting-edge application of extracorporeal membrane oxygenation (ECMO) during oncological thoracic surgery. Therefore, we report the most common surgical procedures in oncological thoracic surgery that can benefit from the use of ECMO. They will be classified and discussed according to the aim of ECMO application. In particular, the use of ECMO is usually limited to certain lung surgery procedures that can be resumed such as in procedures in which an adequate ventilation is not possible such as in single lung patients, procedures where conventional ventilation can cause conflict with the surgical field such as tracheal or carinal surgery, and conventional procedures requiring both ventilators and hemodynamic support. So far, all available evidence comes from centers with large experience in ECMO and major thoracic surgery procedures.